Penerapan Massage Abdomen Terhadap Konstipasi pada Pasien dengan Gangguan Neurologi: CVD di Ruang Unit Stroke - M. Ika Sulistyawati; Aniska Indah Fari; Lilik Pranata (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
The problem that occurs in stroke patients is damage to the autonomic nervous system that regulates intestinal peristalsis, causing a decrease in the defecation reflex and leading to constipation. If constipation is not treated properly, it will affect the quality of life of stroke patients. Constipation can be treated pharmacologically and non-pharmacologically. One non-pharmacological treatment is abdominal massage. Abdominal massage can stimulate the parasympathetic nervous system, which can increase digestive system motility, reduce tension in the abdominal muscles, and have a relaxing effect on the sphincter. The design used in the preparation of the final scientific paper for the nursing study was a one-group pretest-posttest case study with abdominal massage intervention on three respondents who had experienced constipation for ≥ 72 hours. Abdominal massage was given once a day for 10-15 minutes for three consecutive days. The constipation scores using the Constipation Assessment Scale (CAS) were as follows: respondent 1, Mrs. L, from 13 to 6; Mrs. W, from 12 to 11; and Mrs. W, from 15 to 11. There was a decrease in the CAS score before and after the abdominal massage was administered, but it was not yet able to significantly alleviate constipation in stroke patients. The application of this EBP is expected to provide additional information on the administration of abdominal massage to stroke patients experiencing constipation for ≥72 hours.